2016
DOI: 10.1111/imb.12254
|View full text |Cite
|
Sign up to set email alerts
|

Alternative exon‐encoding regions of Locusta migratoria muscle myosin modulate the pH dependence of ATPase activity

Abstract: Whereas the vertebrate muscle myosin heavy chains (MHCs) are encoded by a family of Mhc genes, most insects examined to date contain a single Mhc gene and produce all of the different MHC isoforms by alternative RNA splicing. Here, we found that the migratory locust, Locusta migratoria, has one Mhc gene, which contains 41 exons, including five alternative exclusive exons and one differently included penultimate exon, and potentially encodes 360 MHC isoforms. From the adult L. migratoria, we identified 14 MHC i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 41 publications
(58 reference statements)
0
15
1
Order By: Relevance
“…blastn analysis of outlier loci found within clusters 845 and 632 revealed that the haplotype of 230 bp containing SNP 100240_75 (cluster 845/chromosome 7) exhibits high similarity with a repeat region from Locusta migratoria that correspond to an RTE‐2 retrotransposon (Ruiz‐Ruano et al, 2018) (Table ). Less stringent blastn searches and blastx analysis retrieved homology with myosin and troponin muscle genes (Li et al, 2016; Liang et al, 2020) and with a sulphotransferase enzyme (Chen et al, 2021), all from L . migratoria (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…blastn analysis of outlier loci found within clusters 845 and 632 revealed that the haplotype of 230 bp containing SNP 100240_75 (cluster 845/chromosome 7) exhibits high similarity with a repeat region from Locusta migratoria that correspond to an RTE‐2 retrotransposon (Ruiz‐Ruano et al, 2018) (Table ). Less stringent blastn searches and blastx analysis retrieved homology with myosin and troponin muscle genes (Li et al, 2016; Liang et al, 2020) and with a sulphotransferase enzyme (Chen et al, 2021), all from L . migratoria (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…In this case, S7). Less stringent blastn searches and blastx analysis retrieved homology with myosin and troponin muscle genes (Li et al, 2016;Liang et al, 2020) and with a sulphotransferase enzyme (Chen et al, 2021), all from L. migratoria (Table S7). Outlier loci from cluster 632 did not match with any known sequence.…”
Section: Outlier Loci and Correlation With Environmental Variablesmentioning
confidence: 99%
“…The migratory locust, Locusta migratoria, contains a single Mhc gene comprised of 41 exons, including 5 clusters of alternative exclusive exons and 1 differently included penultimate exon (Fig. 1A) (Li et al, 2016). In the motor domain of locust MHC (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In the tail of locust MHC, the S2 hinge region is encoded by 2 exon-30 variants (30a and 30b) and 2 types of tail tip can be produced by splicing in/out of exon-40. Theoretically, 360 different locust MHC isoforms can be generated by alternative-splicing exons (Li et al, 2016). Remarkably, the regions encoded by the alternative exons of locust Mhc gene are identical to those of Drosophila Mhc gene, indicating that both species use a similar strategy to modulate the motor functions of striated muscle myosin.…”
Section: Introductionmentioning
confidence: 99%
“…Insect flight muscle is generally not believed to express multiple fiber types that differ in MyHC isoform composition (Ayme-Southgate et al, 2015;Hooper and Thuma, 2005) and contractile properties. However, two recent studies suggest that multiple Myhc mRNAs can be expressed in Manduca sexta and Locusta migratoria flight muscle tissue (Ayme-Southgate et al, 2015;Li et al, 2016). Although it is not known whether these mRNAs are translated into functional MyHC protein isoforms for M. sexta, Ziegler et al (1994) reported the presence of two distinct MyHC protein isoforms in flight muscle of L. migratoria (and the fly Phormia terraenovae).…”
Section: Introductionmentioning
confidence: 99%